Driving a Vehicle without a Driving Licence in the New Romanian Criminal Code - ZAZULA, Bela (Journal of Legal Studies, 2016)
Improving the traffic safety represents a central objective of the European Union’s policy in the transports field. The Union has in view an improvement of the traffic safety, having as purpose the diminishing of deaths, bodily injuries and material damages. An important element of this policy is represented by the consistent application of sanctions for transgressing the circulation norms committed in the Union, an objective to which the New Romanian Criminal Code has fallen into line.